Microwave-assisted hydrothermal synthesis and magnetic properties of nanostructured cobalt ferrite - Martinelli, Antonio Eduardo (2021)
Cobalt ferrite is an important magnetic material due to its high saturation magnetization and high energy product BH. CoFe2O4 nanoparticles can be synthesized by a variety of methods that often demand long synthesis times. Using the microwave-assisted hydrothermal method, single-phase CoFe2O4 with controlled crystallite size was rapidly obtained. The effect of a preheating step and mineralizing agent, i.e., NH4OH and KOH, was investigated. Exposure to microwave radiation ranged from 0.5 to 2 h. The formation of CoFe2O4 was confirmed by X-ray diffraction. The average crystallite size of CoFe2O4 nanoparticles was estimated between 5.2 nm and 21.3 nm by Rietveld refinement. The crystallite size depended on the preheating step and mineralizing agent used. Transmission electron microscopy images revealed that CoFe2O4 nanoparticles were nearly spherical when prepared with NH4OH but cubic and spherical when prepared with KOH. Both, hysteresis curves and Mossbauer spectra at room temperature, € showed superparamagnetic behavior for samples with the smaller crystallite size. Samples with larger crystallites consisted of blocked particles and depicted an increase in the MR/MHmax ratio and coercive field, Hc. Distinct magnetic properties resulting from variations in the synthesis parameters yield different applications for nanostructured CoFe2O4